Religion, politics and law : philosophical reflections on the sources of normative order in society - Labuschagne, Barend Christoffel, 1962-; Sonnenschmidt, Reinhard. (Religious Studies, Theology and Philosophy E-Books Online, Collection 2009, ISBN: 9789004223097., 2009)
Modern, liberal democracies in the West living under the rule of law and protection of human rights cannot articulate the very values from which they derive their legitimacy. These pre-political and pre-legal preconditions cannot be guaranteed, let alone be enforced by the state, but constitute nevertheless its moral and spiritual infrastructure. Until recently, a common background and horizon consisted in Christianity, but due to secularisation and globalisation, society has become increasingly multicultural and multireligious. The question can and should be raised how religion relates to these sources of normative order in society, how religion, politics and law relate to each other, and how social cohesion can be attained in society, given the growing varieties of religious experiences. In this book, a philosophical account of this question is carried out, on the one hand historically from Plato to the Enlightenment, on the other hand systematically and practically.